The cultural-historical heritage of Ilijas municipality as the basis for the inclusion in regional tourist flows - Nezirović, Senada; Avdić, Belma; Orić, Muniba (Journal for Geography, 2018)
Many cities in Bosnia and Herzegovina, including Ilijas, are missing the opportunity to earn tourism income, precisely because they do not have the planned promotion of their cultural and historical heritage. Cultural and historical monuments get a real social and tourist value only when involved in tourist movements and when they become accessible to tourists who plan to travel because of them. In this way, cultural and historical monuments exist not only as a source and object of knowledge but also as an indicator of the cultural level of the population and the country as a whole. The subject of this study is the possibility of incorporating the cultural and historical heritage, primarily the Medieval City of Dubrovnik and the necropolis of the tombstones of Koposici, into regional tourist flows with the aim of economic strengthening of the municipality of Ilijas through the tourism development and improvement of promotion of tourist resources and services of the mentioned municipality. The aim of this paper is to analyze the cultural tourist resources of the municipality of Ilijas and their delimitation in the development of tourism of the mentioned municipality. In the delimitation of tourism resources, geographic tourist and economic concepts of valorisation are used, based on which the dominant tourist resources are separated.